2018
DOI: 10.1002/elsc.201800067
|View full text |Cite
|
Sign up to set email alerts
|

Waste fat biodegradation and biomodification by Yarrowia lipolytica and a bacterial consortium composed of Bacillus spp. and Pseudomonas putida

Abstract: Fats, oils, and greases (FOGs) are a particular environmental threat. Biodegradation of FOGs is a challenge and in this study the biodegradation of waste cooking fats, namely butter and olive oil, was studied using a non‐conventional yeast, Yarrowia lipolytica strain LFMB 20, and a bioaugmentation product consisting of Bacillus spp. and Pseudomonas putida CP1 strain. The microorganisms were grown aerobically in shake‐flask experiments in an enriched medium supplemented with ca 0.85% w/v of waste fat. Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Therefore, the ability of Y. lipolytica strains to produce biomass rich in various nutritional components on available cheap carbon sources like oily wastes is highly desired. Furthermore, biodegradation of these wastes is very important for environmental protection (Katre et al 2012;Saygün et al 2014;Vasiliadou et al 2018;Tzirita et al 2018). Additionally, there are no generated wastes according to the take-make-dispose concept (Lopes et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the ability of Y. lipolytica strains to produce biomass rich in various nutritional components on available cheap carbon sources like oily wastes is highly desired. Furthermore, biodegradation of these wastes is very important for environmental protection (Katre et al 2012;Saygün et al 2014;Vasiliadou et al 2018;Tzirita et al 2018). Additionally, there are no generated wastes according to the take-make-dispose concept (Lopes et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…When bacterial consortium reached the stationary phase, lipids previously accumulated were re-consumed. The composition of these microbial lipids were dependent on growth phase, being only composed by unsaturated fatty acids (oleic and linoleic acids) during exponential phase and mainly composed by saturated fatty acids (stearic and palmitic acid) during the late growth phase (Tzirita et al, 2018).…”
Section: Microbial Lipidsmentioning
confidence: 99%
“…The addition of magnesium and phosphate to Y. lipolytica cultures gave rise to an improvement of lipid content (Liu et al, 2015). To enhance the solubility of WCO and its bioavailability to microbial cells, several authors add to the medium chemical surfactants or emulsifiers, such as Tween 80 (Arous et al, 2017;El Bialy et al, 2011;Papanikolaou et al, 2011;Tzirita et al, 2018) or arabic gum (Lopes et al, 2019). However, Patel and Matsakas (2018) found an alternative approach to improve the accessibility of Cryptococcus curvatus cells to the WCO, avoiding the use of chemical compounds.…”
Section: Microbial Lipidsmentioning
confidence: 99%
“…The pork lard was associated for a long time as a potential cause of vascular and heart disease [8] and therefore not used as much in food preparation. The price of animal fat is relatively low, which makes it a cheap and promising substrate for microbial fermentation [9] in order to obtain valuable metabolites (i.e., short-and medium-chain fatty acids) [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, the fermentation of both okara and pork lard in a yeast and lactobacilli co-culture has not been investigated previously. Instead, Tzirita et al (2018) [10] reported on waste fat biodegradation by Y. lipolytica, Bacillus spp. and Pseudomonas putida consortium in order to produce lipids with significant industrial, ecological, and biotechnological interest.…”
Section: Introductionmentioning
confidence: 99%